Defining resilience analytics for interdependent cyber-physical-social networks. Issue 2 (3rd April 2017) - Barker, Kash; Lambert, James H.; Zobel, Christopher W.; Tapia, Andrea H.; Ramirez-Marquez, Jose E.; Albert, Laura; Nicholson, Charles D.; Caragea, Cornelia
Abstract: Theory, methodology, and applications of risk analysis contribute to the quantification and management of resilience. For risk analysis, numerous complementary frameworks, guidelines, case studies, etc., are available in the literature. For resilience, the documented applications are sparse relative to numerous untested definitions and concepts. This essay on resilience analytics motivates the methodology, tools, and processes that will achieve resilience of real systems. The paper describes how risk analysts will lead in the modeling, quantification, and management of resilience for a variety of systems subject to future conditions, including technologies, economics, environment, health, developing regions, regulations, etc. The paper identifies key gaps where methods innovations are needed, presenting resilience of interdependent infrastructure networks as an example. Descriptive, predictive, and prescriptive analytics are differentiated. A key outcome will be the recognition, adoption, and advancement of resilience analytics by scholars and practitioners of risk analysis.